Management of arrythmia in the COVID 19 era - Tomos, Sirma; Schroder, Verginica; Margaritti, Doina; Busuricu, Florica (Technium BioChemMed, 2021)
There is currently well-documented evidence that SARS CoV2 infection is frequently associated with secondary cardiac damage. Although lung damage is a priority, the evolution over time of COVID 19 infection frequently includes cardiovascular complications, the most common being: myocarditis, heart failure and acute coronary syndrome resulting from coronary artery thrombosis or plaque ruptures associated with SARS-CoV-2. Therefore, for the judicious use of resources, both human and material, and for the protection of medical staff, it is necessary to establish standard procedures to limit the contact of medical staff with the infected patient COVID 19.